EXAMINATION OF CRP (C-Reactive Protein) IN OBESE TEENAGERS IN SMA MUHAMMADIYAH 02 MEDAN - Ice Ratnalela Siregar (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2017)
C-Reactive Protein (CRP) is one of the acute phase proteins present in normal serum in very little concentrations synthesized in the liver that play a role in inflammation. Obesity is a state of increase in body fat (adipocyte cells) in which adipocytes will try to maintain energy by releasing proinflammatory cytokines one of them interleukin 6 (IL-6), IL-6 release will induce CRP production in the liver. CRP examination on obese students in SMA Muhammadiyah 02 Medan.This research was conducted descriptively by Latex Aglutination method. This research was conducted at the Laboratory of Poltekkes Kemenkes Medan Health Analyst Department in May 2017 after sampling of students in SMA Muhammadiyah 02 Medan. The population of this research is 30 people of total population of 30 samples.Based on the research that has been done, the result of positive CRP examination is 18 percentage samples are 60% and 12 percent negative sample 40%. Based on sex, the result of positive CRP examination were 13 samples of female sex, 44% and 5 positive samples of male were 17%. Suggested on obese students to regularly exercise and live healthy with healthy foods also to avoid disease.